Britain, Germany and Colonial Violence in South-West Africa, 1884-1919 The Herero and Nama Genocide - Bomholt Nielsen, Mads. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Reflecting emerging scholarship on the entanglement of colonial histories, this book examines British and South African perspectives on, and involvement in, the genocide of the Herero and Nama in German South West Africa from 1904 to 1908. Seeking to present a transnational and trans-colonial perspective on the war imposed by Germany, the book sheds light on Anglo-German relations during 'native' rebellions and exposes shared experiences of colonial violence. This approach aligns with a new surge of historiography which emphasises the co-operation between colonial powers to maintain order in Africa. The author focuses on British involvement in counter-insurgency efforts, its awareness of the extent of the genocide, and how the Herero-Nama War impacted colonial rule in British territory. Not only exploring the war years, the book covers the entire period of German colonial rule in Africa (1884-1919), and highlights British and South African perspectives throughout this period. Offering fresh insights on the first genocide of the century, this book builds on a growing body of research into trans-colonialism and contributes to modern German history.
1. Introduction -- 2. Britain and Germany in South West Africa, 1884-1904 -- 3. The First Genocide of the Twentieth Century -- 4. Concerns and Co-operation: Britain's Involvement in the Rebellion -- 5. Containing African Mobility -- 6. A New Casement Report -- 7. German Colonialism in Paris, 1918-19 -- 8. Conclusion.
Keywords: Imperialism; World history; Europe, Central-History.; Africa, Sub-Saharan-History.; Great Britain-History.; Imperialism and Colonialism; World History, Global and Transnational History; History of Germany and Central Europe; History of Sub-Saharan Africa; History of Britain and Ireland